Enhanced visible-light-driven photocatalytic activities of Bi2Fe4O9/g-C3N4 composite photocatalysts. (August 2018) - Wang, Geming; Liu, Shutong; He, Tiancheng; Liu, Xuan; Deng, Quanrong; Mao, Yangwu; Wang, Shenggao
Graphical abstract: The Z-scheme mechanism is proposed in Bi2 Fe4 O9 /g-C3 N4 composites. The photoinduced electrons in the CB of Bi2 Fe4 O9 will move to the VB of g-C3 N4 and recombine with those holes in its VB. The holes of Bi2 Fe4 O9 and electrons of g-C3 N4 can be efficiently separated from each other. Those separated electrons in the VB of Bi2 Fe4 O9 and those separated holes in the CB of g-C3 N4 can carry out the reduction and oxidation reactions of RhB, which leads to the improved visible-light-driven photocatalytic activities compared with those of its single components. Highlights: The novel Bi2 Fe4 O9 /g-C3 N4 composite photocatalysts have been designed and prepared. Combination of Bi2 Fe4 O9 and g-C3 N4 could enhance the visible-light-driven photocatalytic degradation for RhB. The effects of Bi2 Fe4 O9 /g-C3 N4 weight ratios on photocatalytic performance in the composite have been discussed. The Z-scheme photocatalytic mechanism was proposed and discussed in detail. Abstract: A series of Bi2 Fe4 O9 /g-C3 N4 composite photocatalysts are prepared via a facile mixing-calcination method. The crystal structures of composites are investigated by X-ray Diffraction (XRD) and Fourier Transform Infrared Spectroscopy (FT-IR). The Field Emission Scanning Electron Microscope (FE-SEM) in combination with Energy Dispersive X-ray Spectroscopy (EDS) mapping analysis and Transmission Electron Microcopy (TEM) images illustrate the uniform distribution of constituent elements and clear interface between Bi2 Fe4 O9 and g-C3 N4 component. The visible-light-driven photocatalytic rates of Rhodamine B over Bi2 Fe4 O9 /g-C3 N4 composites increase and then decrease with the increase of g-C3 N4 content. The effects of Bi2 Fe4 O9 /g-C3 N4 weight ratios on photocatalytic performance are thoroughly discussed. Meanwhile, the active species trapping experiments and the electrochemical impedance spectra as well as the electronic energy-band structure estimation analysis demonstrate that the photocatalytic mechanism for Bi2 Fe4 O9 /g-C3 N4 composites is ascribed to the Z-scheme. In addition, the recyclability and stability experiments of the composite are also studied.